METODE ZIG-ZAG DALAM MENINGKATKAN LATIHAN TEKNIK DASAR DRIBLING PADA PERMAINAN SEPAK BOLA SISWA KELAS V DI SD NEGERI 4 KECAPI KABUPATEN JEPARA - Hilmy Aliriad; Ainu Zuhriyah; Imam Nor Rif’an (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2016)
Dribbling is one of the basic techniques that has quite an important role in the game of football, it is not surprising if football observers specifically state that the skill of a player can be seen in how a player dribbles the ball. The problem in this study is "whether the zig-zag method can improve the basic technical skills of dribling in football games in SD Negeri 4 Kecapi?" The study aims to determine the level of basic dribling techniques using the zig-zag method in football games at SD Negeri 4 Harp. This research is a PTK research, this class action research (CAR) is an action research conducted by a teacher with the aim to improve the quality of the implementation of classroom learning. Based on data processing taken using tests and measurements. The results of the study that as many as 18 students in the second cycle or 78.26% had completed learning compared to the data value of the first cycle of 8 students or 34.78%, and the second cycle of 5 students or 21.74% had not been completed compared to the value of the cycle I, 15 students or 65.22%. The results concluded that mendribble training was effective in increasing the ability of significant skills in zig-zag herding practice towards ability in soccer games at SDN 4 Kecapi.